The role of private developers in local infrastructure provision in Malaysia - Salleh, Dani; Okinono, Otega (2016)
Globally, the challenge of local infrastructure provision has attracted much debate amongst different nations including Malaysia, on how to achieve an effective and efficient infrastructural management. This approach therefore, has intensified the efforts of local authorities in incorporating private developers in their developmental agenda in attaining a sustainable infrastructural development in local areas. Basically, the knowledge of the need for adequate provision of local infrastructure is well understood by both local and private authorities. Likewise, the divergent opinions on the usage of private delivery services. Notwithstanding the common perception, significant loopholes have been identified on the most appropriate and ideal approach and practices to adopt in enhancing local infrastructure development. The study therefore examined the role of private developers in local infrastructure provision and procedure adopted by both local authorities and the privates sector in local infrastructure development. Data was obtained using the questionnaire through purposive sampling, administered to 22 local authorities and 16 developers which was descriptively analysed. Emanating from the study findings, the most frequently approved practices by local authorities are joint venture and complete public delivery systems. Likewise, negotiation was identified as a vital tool for stimulating the acquisition of local infrastructure provision. It was also discovered the one of the greatest challenge in promoting private sector involvement in local infrastructure development is due to unregulated-procedure. The study therefore recommends, there is need for local authorities to adopt a collective and integrated approach, nevertheless, cognisance and priority should be given to developing a well-structured and systematic process of local infrastructure provision and development.